HUBUNGAN PERSEPSI STEREOTIP GENDER DENGAN PRESENTASI DIRI SISWA DI SMA NEGERI 1 MUARO JAMBI - Setiawati, Evi; Harahap, Nur Hasanah; Gutji, Nelyahardi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research aims to reveal the relationship between gender stereotype perceptions and students' self-presentation at SMA Negeri 1 Muaro Jambi. This research is limited only to gender stereotyped views of students' daily life at school. This type of research is quantitative research with correlational methods. The sample in this research was students in classes X and The instruments used were gender stereotype questionnaires and student self-presentation questionnaires. Data were analyzed using the Percentage Test with formula C, statistical assumption test, and Correlation Test. The research results show that: 1) the level of perception of gender stereotypes of students at SMA Negeri 1 Muaro Jambi is in the high category with a percentage of 78%. 2) students' self-presentation at SMA Negeri 1 Muaro Jambi is in the high category with a percentage of 74%. 3) The research results also show that the correlation results are known to be positive at 0.414 > r table 0.138 with a sig result of 0.000 < 0.05. The Pearson correlation value obtained is interpreted using correlation guidelines, where the calculated r (0.414) is in the range (0.40 – 0.70) which is interpreted as falling into the category of having an adequate relationship. So it can be concluded that there is a significant relationship in the positive direction between perceptions of gender stereotypes and students' self-presentation.